Therapeutic Targeting of the IGF Axis - Osher, Eliot; Macaulay, Valentine M. (Cells (Basel, Switzerland), 2019)
The insulin like growth factor (IGF) axis plays a fundamental role in normal growth and development, and when deregulated makes an important contribution to disease. Here, we review the functions mediated by ligand-induced IGF axis activation, and discuss the evidence for the involvement of IGF signaling in the pathogenesis of cancer, endocrine disorders including acromegaly, diabetes and thyroid eye disease, skin diseases such as acne and psoriasis, and the frailty that accompanies aging. We discuss the use of IGF axis inhibitors, focusing on the different approaches that have been taken to develop effective and tolerable ways to block this important signaling pathway. We outline the advantages and disadvantages of each approach, and discuss progress in evaluating these agents, including factors that contributed to the failure of many of these novel therapeutics in early phase cancer trials. Finally, we summarize grounds for cautious optimism for ongoing and future studies of IGF blockade in cancer and non-malignant disorders including thyroid eye disease and aging.